Totalitas Pelayanan Pastoral dan Spiritualitas Kenabian dalam Konteks Paroki Boganatar: Telaah Biblis atas Yohanes 6:1-15 - Sebo, Ferdinandus; Uskono, Yosep; Kasiwali, Yulius Candra (Faculty of Theology Duta Wacana Christian University, 2025)
AbstractThis study offers a theological reflection on prophetic spirituality in pastoral ministry, grounded in the pericope of John 6:1–15 and contextualized within the pastoral reality of St. John the Baptist Parish, Boganatar, Diocese of Maumere. Employing a descriptive qualitative methodology, the research interprets Jesus’ act of feeding the five thousand as a paradigm of prophetic ministry that embodies compassion, participation, and transformation. Thefindings suggest that prophetic spirituality is characterized by a profound sensitivity to the concrete needs of the faithful, active participation in the life of the community, and a total self-donation rooted in the example of Christ. Within the rural pastoral context, such spirituality becomes a vital framework for fostering a ministry that is both responsive to human suffering and liberative in its orientation. The study contributes to pastoral praxis by deepening the integration of Gospel values into the life of the local Church, thereby promoting a ministry that humanizes, empowers, and transforms the community of faith. AbstrakPenelitian ini bertujuan untuk merefleksikan spiritualitas kenabian dalam pelayanan pastoral berdasarkan Yohanes 6:1-15, dengan fokus pada konteks pastoral Paroki St. Yohanes Pembaptis Boganatar, Keuskupan Maumere. Melalui pendekatan kualitatif deskriptif, kajian ini menyoroti bagaimana teladan Yesus yang memberi makan lima ribu orang menjadi inspirasi dalam mewujudkan pelayanan yang transformatif. Hasil penelitian menunjukkan bahwa spiritualitas kenabian menuntut kepekaan terhadap kebutuhan umat, keterlibatan aktif dalam pelayanan, dan pemberian diri yang total. Dalam konteks pastoral pedesaan, spiritualitas ini relevan untuk membangun pelayanan yang responsif dan membebaskan. Eksplorasi ini memberikan kontribusi penting bagi praksis pastoral Gereja lokal agar semakin berakar pada nilai-nilai injili yang memanusiakan dan memberdayakan umat.